2008
DOI: 10.1248/cpb.56.843
|View full text |Cite
|
Sign up to set email alerts
|

New Germacrane Sesquiterpenes from Salvia chinensis

Abstract: Two new germacrane sesquiterpenes, called salviadienol A (1) and salviadienol B (2), together with five known compounds, methyl-ent-4-epi-agath-18-oate (3), angelicoidenol (4), clovane-2b b,9a a-diol (5), dehydrovomifoliol (6) and blumenol A (7), were isolated from Salvia chinensis. Their structures were identified on the basis of spectral characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Salviadienol A ( 2 ) and salviadienol B ( 6 ) were the first germacrane sesquiterpenes obtained from S. chinensis . Compounds 2 and 6 were highly acetylated members with oxy-isovaleryl groups being the most unusual ones . From the whole plant of S. roborowskii , four new germacrane sesquiterpene esters, 3 , 4 , 5 , and 16 , were isolated in 2003 .…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salviadienol A ( 2 ) and salviadienol B ( 6 ) were the first germacrane sesquiterpenes obtained from S. chinensis . Compounds 2 and 6 were highly acetylated members with oxy-isovaleryl groups being the most unusual ones . From the whole plant of S. roborowskii , four new germacrane sesquiterpene esters, 3 , 4 , 5 , and 16 , were isolated in 2003 .…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Compounds 2 and 6 were highly acetylated members with oxy-isovaleryl groups being the most unusual ones. 42 From the whole plant of S. roborowskii, four new germacrane sesquiterpene esters, 3, 4, 5, and 16, were isolated in 2003. 43 In 2005, the same compound 16 was isolated from S. castanea Diels f. tomentosa Stib again and given another name: castanin B (16).…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
“…The coupling patterns of the H-6 (dd, J = 7.0, 3.6 Hz) and H-5α (dd, J = 11, 3.6 Hz); H-6‴ (dd, J = 7.0, 3.6 Hz) and H-5‴α (dd, J = 11, 3.6 Hz) led to confirmation of the cis -orientation of H-6/H-5α and H-6‴/H-5‴α [20,21], which are in line with those of 4-[2-(β- d -glucopyranosyloxy)ethyl]-4-hydroxy-5-methoxy-2-cyclohexen-1-one that was obtained from M. hortensis [19], and 1,6-dihydroxy-4-oxo-2-cyclohexene-1-cetic acid ethyl ester isolated from Senecio scandens [17], and thus the configuration of C-6 and C-6‴ were determined as S and S . Analysis of the 13 C NMR data of C-1 and C-1‴ in 4 indicated that they were greatly similar to that of C-1 (δ C 71.8) in 4-[2-(β- d -glucopyranosyloxy)ethyl]-4-hydroxy-5-methoxy-2-cyclohexen-1-one [19], and our compound 4 showed in MeOH of −26.4°, which is in accord with that observed in 1,6-dihydroxy-4-oxo-2-cyclohexene-1-acetic acid ethyl ester ( −12.5°) [17].…”
Section: Resultsmentioning
confidence: 99%
“…In the NOESY spectrum (Figure 3), the key NOE correlations of H-9/H-10 and H-6/H-11 showed that H-9 and H-10, H-6 and H-11 were on the same face, so the relative stereochemistry was determined. The coupling patterns of the H-9 (dt, J = 3.0 and 6.5 Hz) and H-10 (d, J = 3.0 Hz) led to confirmation of the cis -orientation of H-9/H-10 and possessed β -orientation [17], and thus the configuration of C-9 and C-10 were determined as R* and S* , respectively. The sign of [ α ] D for proline-containing DKPs is either negative or positive, depending only on the absolute configuration of Pro [12].…”
Section: Resultsmentioning
confidence: 99%